Effect of heat treatment conditions on properties of lead- free Bi2GeO5ferroelectric glass ceramics - P. Kantha (2018)
Nowadays, lead-free ferroelectric materials have attracted much interest among materials scientists as a result of environmental concern. The bismuth germanate (Bi2GeO5) phase, one of the lead-free ferroelectric crystals, is of particular interest as its composition already contains good glass former (GeO2) and can be prepared by an alternative glass ceramic route. In this work, the conventional melt-quenching method was used to produce the parent glass with composition of 60 mol% BiO1.5: 20 mol% GeO2: 20 mol% BO1.5. The as-received glass pieces were subjected to the heat treatment schedule at various crystallization temperatures and dwell-times. The glass and glass ceramics samples were then investigated by XRD, Raman spectroscopy and their dielectric properties were also measured. The XRD and Raman spectroscopy showed that the crystallinity of the prepared glass ceramics depended very much on crystallization temperature and dwell-time. The larger dielectric constant and lower dielectric loss were obtained as crystallinity of the glass ceramics enhanced. The highest dielectric constant (εr) was found at 77 with a low dielectric loss of about 0.005. © 2009 American Institute of Physics.